2021
DOI: 10.1088/1748-9326/ac018e
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from food systems: building the evidence base

Abstract: New estimates of greenhouse gas (GHG) emissions from the food system were developed at the country level, for the period 1990–2018, integrating data from crop and livestock production, on-farm energy use, land use and land use change, domestic food transport and food waste disposal. With these new country-level components in place, and by adding global and regional estimates of energy use in food supply chains, we estimate that total GHG emissions from the food system were about 16 CO2eq yr−1 in 2018, or one-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 33 publications
3
76
0
1
Order By: Relevance
“…Emissions from energy use in agriculture are only about onefifth of the total in CO 2 eq generated from crop and livestock production (Tubiello et al, 2021); however, they represent an important contribution in terms of CO 2 gas, with the other process emitting CO 2 on the farm being the drainage of organic soils. They are therefore of great importance to GHG mitigation in agriculture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emissions from energy use in agriculture are only about onefifth of the total in CO 2 eq generated from crop and livestock production (Tubiello et al, 2021); however, they represent an important contribution in terms of CO 2 gas, with the other process emitting CO 2 on the farm being the drainage of organic soils. They are therefore of great importance to GHG mitigation in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Other uses beyond the farm may include power for forestry ma-chinery and fishing vessels (Dubois et al, 2017). On-farm energy use is a significant component of agricultural production and growth (Sims and Flammini, 2014;Utz, 2011); however, it often attracts less attention in food-related emissions analysis relevant to national determined contributions (Tubiello et al, 2021) as the on-farm energy use emissions are reported instead under the "energy" sector of the national greenhouse gas (GHG) inventories. In fact, countries regularly submit to the UN Framework Convention on Climate Change (UNFCCC), containing only non-CO 2 emissions from crop and livestock biophysical processes, for instance, enteric fermentation in ruminants or nitrous oxide from fertilizers on cropland (IPCC, 2006;Tubiello, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the EAT-Lancet Commission found that shifting to a universal healthy reference diet-rich in fruits, vegetables, whole grain, legumes and low in red meat-could help prevent about 11 million deaths per year by 2050 [68]. These dietary shifts would also reduce emissions from ruminant animals such as beef and dairy cattle, which are the primary sources of on-farm greenhouse gas emissions from food production [69]. The health benefits of reduced red meat consumption may be more pronounced in high-income countries where excess meat consumption is common and should not overshadow the fact that livestock provide an essential nutrient source for people in many low-and middle-income countries [70].…”
Section: Improved Nutrition and Food Securitymentioning
confidence: 99%
“…Nitrous oxide (N2O) is a potent greenhouse gas (GHG) that contributes to global warming and mainly stems from agricultural soils [1]. Agricultural activities are responsible for an estimated two-thirds of the total anthropogenic N2O emissions in the world [2].…”
Section: Introductionmentioning
confidence: 99%